2013
DOI: 10.1371/journal.pone.0075885
|View full text |Cite
|
Sign up to set email alerts
|

Four MicroRNAs Promote Prostate Cell Proliferation with Regulation of PTEN and Its Downstream Signals In Vitro

Abstract: BackgroundPhosphatase and tensin homologue (PTEN), as a tumor suppressor, plays vital roles in tumorigenesis and progression of prostate cancer. However, the mechanisms of PTEN regulation still need further investigation. We here report that a combination of four microRNAs (miR-19b, miR-23b, miR-26a and miR-92a) promotes prostate cell proliferation by regulating PTEN and its downstream signals in vitro.Methodology/Principal FindingsWe found that the four microRNAs (miRNAs) could effectively suppress PTEN expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 58 publications
2
72
0
1
Order By: Relevance
“…PTEN is the target of certain cellular miRNAs, including miR-19a/b [30], miR-29a [31], miR-214 [32], miR-205 [33] and miR-494 [34], which can directly suppress the expression of PTEN in a post-transcriptional manner. An inverse correlation between PTEN and miR-92 expression has been observed in many human cancer tissues, which typically express low levels of PTEN protein and high levels of miR-92a [1921]. In the present study, we found that miR-92a overexpression enhanced endothelial cell viability under oxidative stress via augmenting Akt signaling, suggesting a vasculoprotective effect that is likely mediated through a PTEN-dependent mechanism.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…PTEN is the target of certain cellular miRNAs, including miR-19a/b [30], miR-29a [31], miR-214 [32], miR-205 [33] and miR-494 [34], which can directly suppress the expression of PTEN in a post-transcriptional manner. An inverse correlation between PTEN and miR-92 expression has been observed in many human cancer tissues, which typically express low levels of PTEN protein and high levels of miR-92a [1921]. In the present study, we found that miR-92a overexpression enhanced endothelial cell viability under oxidative stress via augmenting Akt signaling, suggesting a vasculoprotective effect that is likely mediated through a PTEN-dependent mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…An inverse correlation between the expression levels of PTEN and miR-92 has been reported in many human cancer tissues [1921]. To investigate whether PTEN is a target of miR-92a, we analyzed PTEN protein levels in mi-RNA transfected HUVEC cells by western blot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative regulators include MKK-4 (mitogen activated protein kinase kinase-4), TGF-β (transforming growth factor beta), NFκB (nuclear factor of kappa light polypeptide gene enhancer in B-cells), transcriptional cofactor c-JUN and oncogene BMI1; these were shown to suppress PTEN expression in several cancer models (Gericke et al, 2006;Lau et al, 2011;Meng et al, 2012). Many miRNAs are also known to impact on PTEN expression and function in both normal and pathological conditions (Tian et al, 2013). Posttranslational modifications such as active site oxidation, acetylation, phosphorylation, and ubiquitination can also regulate PTEN activity (Gericke et al, 2006;Tamguney and Stokoe, 2007).…”
Section: Regulation Of Pten Expressionmentioning
confidence: 99%
“…Durante os últimos anos, o papel dos miRNAs na regulação da EMT e nas vias de sinalização associadas a esse processo têm sido observado em vários contextos de tumores humanos, dentre eles o miR-10b (MA; TERUYA-FELDSTEIN;WEINBERG, 2007), miR26a (DONG et al, 2014TIAN et al, 2013), miR-29 (RU et al, 2012), miR-34 (LIU et al, 2011SIEMENS et al, 2011;XU et al, 2014), miR-let7 (YU et al, 2007), miR-145 (HU et al, 2014) e miR-146a (ZHONG et al, 2010.…”
Section: Snail+tgf-β2 Foi Confirmadounclassified